2016
DOI: 10.1080/00325481.2016.1131106
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin in the prevention of cardiovascular events in patients with diabetes

Abstract: Diabetes imparts a substantial increased risk for cardiovascular disease-related mortality and morbidity. Because of this, current medical guidelines recommend prophylactic treatment with once-daily, low-dose aspirin (acetylsalicylic acid) for primary and secondary prevention of cardiovascular (CV) events in high-risk patients. However, only modest reductions in CV events and mortality have been observed with once-daily aspirin treatment in patients with diabetes, including patients with a previous CV event, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 113 publications
(153 reference statements)
1
3
0
Order By: Relevance
“…Aspirin is a classic antiplatelet drug that reduces the risk of cardiovascular events in patients with diabetes through the irreversible inhibition of cyclooxygenase (COX)-1, a key enzyme involved in vascular clot formation. 38 In our study, we found increased platelet aggregation rate and high level of CD62p under GV in vitro and in vivo , respectively. Notably, the ability of PAE to alleviate platelet hyperaggregability induced by GV was similar to that of aspirin.…”
Section: Discussionsupporting
confidence: 57%
“…Aspirin is a classic antiplatelet drug that reduces the risk of cardiovascular events in patients with diabetes through the irreversible inhibition of cyclooxygenase (COX)-1, a key enzyme involved in vascular clot formation. 38 In our study, we found increased platelet aggregation rate and high level of CD62p under GV in vitro and in vivo , respectively. Notably, the ability of PAE to alleviate platelet hyperaggregability induced by GV was similar to that of aspirin.…”
Section: Discussionsupporting
confidence: 57%
“…However, no effective prevention of CV events by the administration of low-dose aspirin has been shown earlier, which might have been caused by the existence of resistance 11. Therefore, owing to its effectiveness in the prevention of CV events and improvement of the survival of diabetic patients, clopidogrel may be able to successfully replace aspirin as an attractive therapeutic option in this respect 11. Evidence revealed that clopidogrel treatment contributed to a greater improvement in the renal function and the inflammatory burden than that with aspirin 30, 31.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, low-dose aspirin has been recommended for primary and secondary prevention of CV events in diabetic patients 26. However, no effective prevention of CV events by the administration of low-dose aspirin has been shown earlier, which might have been caused by the existence of resistance 11. Therefore, owing to its effectiveness in the prevention of CV events and improvement of the survival of diabetic patients, clopidogrel may be able to successfully replace aspirin as an attractive therapeutic option in this respect 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation